Menstrual cycle impacts adipokine and lipoprotein responses to acute high-intensity intermittent exercise bout - Olean-Oliveira, Tiago [UNESP]; Figueiredo, Caique [UNESP]; de Poli, Rodrigo Araújo Bonetti [UNESP]; Lopes, Vithor Hugo Fialho [UNESP]; Jimenez-Maldonado, Alberto; Lira, Fábio Santos [UNESP]; Antunes, Barbara Moura [UNESP] (Springer Nature, 2022)
Due to hormonal fluctuation, the menstrual cycle impacts inflammatory response and lipid metabolism; moreover, the anti-atherogenic and anti-inflammatory effects of exercise in this cycle, mainly high-intensity intermittent exercise (HIIE), need to be examined. Therefore, the aim of the current study was to investigate the influence of menstrual cycle phases on adipokine and lipoprotein responses after acute HIIE sessions in healthy women. Fourteen women (age: 24 ± 2 years; BMI: 22.79 ± 1.89 kg·m2) were recruited to perform two HIIE sessions (10 × 1 min running at 90% of maximum aerobic velocity, with 1 min recovery); one during the follicular phase (FP) and other during the luteal phase (LP), randomly. Blood samples were collected at rest, immediately, and 60 min after HIIE sessions. Macrophage inflammatory protein-1α (MIP-1α), leptin, adiponectin, total cholesterol, triacylglycerol (TAG), HDL-c, and glucose concentrations were analyzed. At rest, higher MIP-1α concentrations were observed during the LP compared to FP (p = 0.017). Likewise, leptin (p = 0.050), LDL-c (p = 0.015), and non-HDL (p = 0.016) were statistically higher in the LP. In contrast, the adiponectin/leptin ratio was lower in the LP compared to the ratio found in the FP (p = 0.032). Immediately post-HIIE sessions, in both menstrual phases, higher TAG (p = 0.001) and HDL-c (p = 0.001) concentrations were found, which returned to resting levels after 60 min. In conclusion, adipokine and lipoprotein responses after a single HIIE session are regulated by the phase of the menstrual cycle, contributing to inflammatory conditions, and demonstrating the importance of considering the phases of the menstrual cycle for the periodization of physical training.
Keywords: Follicular phase; Inflammation; Luteal phase; Metabolism; Women health